Manifestaciones poéticas de la identidad en la literatura de autores neoalemanes: ¿a qué llamamos literatura intercultural? - Rossell, Anna (Revista de Filología Alemana, 2007)
As a consecuence of migration and political exile german literature has become richer since many years ago. Authors of these collectives write in german which has derived into a polemic about adequate terminology for this literature. The present article analyses the problematic and his causes, proposes a suitable treatment and studies the cristalisation of cultural identity on the basis of the literature of Emine Sevgi Özdamar.